Design and Implementation of Single-Layer 4 × 4 and 8 × 8 Butler Matrices for Multibeam Antenna Arrays - George A. Adamidis; Ioannis O. Vardiambasis; Melina P. Ioannidou; Theodoros N. Kapetanakis (International Journal of Antennas and Propagation)
Single-layer 4 × 4 and 8 × 8 Butler matrices (BMs) that operate in the L and S bands are implemented in this paper. Easy-to-fabricate microstrip layout topologies are designed and constructed; the final arrangement of the BMs allows realization without any crossovers. The performance of the networks is evaluated by measuring their frequency response. The return loss (RL) and the isolation are below -15 dB over the operation bandwidth for all structures, whereas the average insertion loss is less than 1 dB for the 4 × 4 BM and does not exceed 3 dB for the 8 × 8 BM. The amplitude imbalance is at most 0.5 dB and 1.5 dB, for the 4 × 4 and the 8 × 8 BMs, respectively. Moreover, multibeam antenna arrays fed by the BMs are constructed. The radiation patterns are measured and compared with theoretical data; a good agreement is achieved. The side lobes are sufficiently low, compared to the theoretical predictions, whereas they are further reduced by applying appropriate excitation schemes to the input ports of the BMs.